Fine-tuning optical and electronic properties of graphene oxide for highly efficient perovskite solar cells. Issue 24 (28th June 2015) - Liu, Tongfa; Kim, Dongcheon; Han, Hongwei; Mohd Yusoff, Abd. Rashid bin; Jang, Jin
<x xml:space="preserve">Abstract</x> Simplifying the process of fine-tuning the electronic and optical properties of graphene oxide (GO) is of importance in order to fully utilize it as the hole interfacial layer (HIL).